2008
DOI: 10.1055/s-0028-1087479
|View full text |Cite
|
Sign up to set email alerts
|

Selective Reactions on the Azido Groups of Aromatic Polyazides

Abstract: Aromatic azides are widely used as starting materials in organic synthesis and as photoaffinity labeling reagents in molecular biology. When aromatic azides have two or more nonequivalent azido groups, these groups can selectively react with dipolarophiles, nucleophiles, and reductants or undergo selective thermolysis and photolysis. Such selective reactions open up principally new ways for the directed synthesis of organic compounds and the use of aromatic azides as photoaffinity labeling reagents. This accou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…Aromatic polyazides are widely used as starting materials in organic synthesis and as photoactive cross‐linking reagents in polymer chemistry and lithography . When aromatic polyazides have two or more nonequivalent azido groups, these groups can selectively react with dipolarophiles, electrophiles, nucleophiles and reductants or undergo selective thermolysis and photolysis . Recently, we have reported the synthesis and some chemical transformations of triazides 1–6 (Scheme ) .…”
Section: Introductionmentioning
confidence: 99%
“…Aromatic polyazides are widely used as starting materials in organic synthesis and as photoactive cross‐linking reagents in polymer chemistry and lithography . When aromatic polyazides have two or more nonequivalent azido groups, these groups can selectively react with dipolarophiles, electrophiles, nucleophiles and reductants or undergo selective thermolysis and photolysis . Recently, we have reported the synthesis and some chemical transformations of triazides 1–6 (Scheme ) .…”
Section: Introductionmentioning
confidence: 99%
“…past decades, 8,59,79,80,82,94,98,99 whereas the chelating behavior of donor-functionalized 3H-1,2,3,4-triaza-phosphole derivatives is still practically uncharted. [100][101][102] Clearly speaking, the click reaction between donor-functionalized azides and phosphaalkynes enables access to polydentate ligands, so that we can adjust the stereoelectronic properties based on the additional phosphorus heteroatom and the nature of the substituents. However, few investigations have been performed on the inuence of an additional heteroatom on the properties of triazole derivatives.…”
mentioning
confidence: 99%
“…One of the most interesting features of 2,4,6‐triazidopyridines is a chemical non‐equivalence of the α‐azido and γ‐azido groups. Extensive studies have shown that reactions of triazide 1 with electron‐rich reagents occur selectively on the most electron‐deficient γ‐azido group, while reactions of electron‐poor reagents with 1 take place selectively on the α‐azido groups (Scheme ) . The different reactivity of the α‐azido and γ‐azido groups of 2,4,6‐triazidopyridines correlates well with the 15 N chemical shifts of the N α signals of these groups .…”
Section: Resultsmentioning
confidence: 98%